PERSENTASE SERANGAN HAMA Brontispa longissima (Gestro) PADA TANAMAN KELAPA (Cocos nucifera L.) VARIETAS GENJAH RAJA DAN VARIETAS DALAM BIDO DI BALAI PENELITIAN TANAMAN PALMA MAPANGET - Tirsa Salasa; Caroulus S. Rante; Daisy Kandowangko (COCOS, 2022)
ABSTRACTThis study aims to determine the percentage of pest attack Brontispa longissima (Gestro) oncoconut (Cocos nucifera L.) varieties Genjah Raja and varieties Dalam Bido. The results of the studyare expected to provide information or knowledge to the public regarding the percentage of pestsAttacks B. longissima on coconut so that B. longissima pests can be controlled. The research wascarried out in the coconut plantation area of the Palma Research Institute (Balit Palma) MapangetDistrict, North Minahasa Regency. The research took place from March to July 2021. The researchwas conducted in the form of a survey or by direct observation at the research site. The study wasconducted at the Experimental Garden of Mapanget on coconuts of Genjah Raja and Dalam Bidovarieties with a land area of Â± 0,2 hectares for each variety, then divided into five sub-plots ofobservations spread diagonally. The things that were observed in this study included the symptoms ofthe attack, the plants that were attacked, the fronds that were attacked and the category of attack.The results showed that the percentage of B. longissima pest attack on coconuts in the Dalam Bidovariety was 20% and the Genjah Raja variety was 12.5%. The percentage of midrib that was attackedby B. longissima in the Dalam Bido variety was 17.99% and the Genjah Raja variety was 10.91%.Keyword : Percentage, B. longissima, Coconut